The Tradition of Maantaan Padi Jo Mangubang in Situmbuk Village, Salimpaung District, Tanah Datar Regency, West Sumatra - Fitri, Anisa; Suharti (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research is entitled "Tradition of Maantaan Padi Jo Mangubang in Nagari Situmbuk, Salimpaung District, Tanah Regency, West Sumatra" This research aims to find out about the process of implementing maantaan padi jo mangubang in Nagari Situmbuk. And in this research also aims to describe the symbolic meanings contained in the tradition of maantaan padi jo mangubang. The theory used in this research is the symbolic interpretative theory of Clifford Geertz. The method used in this research is a qualitative method. The results of this research explain the background of the tradition of maantaan padi jo mangubang in Nagari Situmbuk, that the history of maantaan padi jo mangubang is divided into two activities, namely maantaan padi and mangubang. Maantaan padi began in the 1640s. Meanwhile, mangubang was carried out several months after the creation of maantaan padi, the person who first made the kubang of the bride's family named Mayang Sani. This tradition begins with several processions, namely determining the time of marriage, the bundo kanduang meeting, pre-wedding processes, the wedding time, maantaan padi, mangubang and manampuah. Behind this, this tradition turns out to have a general meaning, namely the meaning of family and kinship. As for other meanings, there are symbolic meanings such as the meaning of rice meaning the first livelihood, the meaning of sumpik minciang meaning the woman who is married is ready to be accommodated by the man's family. The meaning of Ceret means that marriage begins with pure intentions, the meaning of Mangubang means repairing a strained bond. The meaning of Kubang means that the man and woman are united in the bonds of the household. The meaning of sticky rice means prayers for a close-knit household and grated coconut means the sweet, salty and bland life after marriage. Finally, the meaning of the basin means being ready to accept the risks of good and bad after marriage.